ARISupport - Interaction support for augmented reality systems - Lopes, Luiz Fernando Braga; Sementille, Antonio Carlos [UNESP]; Brega, José Remo Ferreira [UNESP]; Marques, Fátima L. S. Nunes; Rodello, Ildeberto Aparecido (Springer Nature, 2005)
The communication between user and software is a basic stage in any Interaction System project. In interactive systems, this communication is established by the means of a graphical interface, whose objective is to supply a visual representation of the main entities and functions present in the Virtual Environment. New ways of interacting in computational systems have been minimizing the gap in the relationship between man and computer, and therefore enhancing its usability. The objective of this paper, therefore, is to present a proposal for a non-conventional user interface library called ARISupport, which supplies ARToolKit applications developers with an opportunity to create simple GUI interfaces, and provides some of the functionality used in Augmented Reality systems. © Springer-Verlag Berlin Heidelberg 2005.
Keywords: ARISupport; Computational systems; User and software; Visual representation; Computer aided software engineering; Decision support systems; Digital libraries; Graphical user interfaces; Interactive computer systems; Virtual reality